2023
DOI: 10.1007/s40120-023-00460-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Societal Value of Lecanemab in Patients with Early Alzheimer’s Disease Using Simulation Modeling

Abstract: Introduction: Alzheimer's disease (AD) is a progressive neurodegenerative disorder associated with memory, cognitive, and behavioral deficits, and brings significant economic burden on caregivers and healthcare systems. This study aims to estimate the long-term societal value of lecanemab plus standard of care (SoC) versus SoC alone, corresponding to a range of willingness-to-pay (WTP) thresholds based on the phase III CLARITY AD trial readouts from both the US payer and societal perspectives. Methods: An evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Whittington et al (40) showed a lower incremental cost-effectiveness ratio with aducanumab treatment stopping at an earlier severity state and diminished outcomes with stronger treatment effect waning assumptions. AD-ACE model applications (22,34,41) showed higher lecanemab treatment value with higher discontinuation rates, with maintained reduced amyloid level after stopping treatment and with lower dosing frequency while assuming no treatment effect waning, and lower lecanemab treatment value with shorter maximum treatment duration. Kongpakwattana et al (42) showed a higher cost-effectiveness ratio with earlier stopping donepezil at severe dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whittington et al (40) showed a lower incremental cost-effectiveness ratio with aducanumab treatment stopping at an earlier severity state and diminished outcomes with stronger treatment effect waning assumptions. AD-ACE model applications (22,34,41) showed higher lecanemab treatment value with higher discontinuation rates, with maintained reduced amyloid level after stopping treatment and with lower dosing frequency while assuming no treatment effect waning, and lower lecanemab treatment value with shorter maximum treatment duration. Kongpakwattana et al (42) showed a higher cost-effectiveness ratio with earlier stopping donepezil at severe dementia.…”
Section: Discussionmentioning
confidence: 99%
“…The second use case is the cross-validation of a model published by Tahami Monfared et al (22) which was funded by Eisai, the sponsor of the lecanemab phase 3 trial. They used the Alzheimer's Disease ACE Simulator (AD-ACE) model (32) which uses a patient-level microsimulation approach capturing domains for AD pathology (e.g., beta-amyloid biomarkers), cognition, function, behavior and dependency.…”
Section: Use Case 2: Cross-validate Existing Ad-ace Modelmentioning
confidence: 99%
See 1 more Smart Citation